Ovarian stimulation with letrozole in nulliparous young women with relapsing early-stage serous borderline ovarian tumors - Valeria Lombardi Fäh; Federico Del Vento; S. Intidhar Labidi-Galy; Manuela Undurraga (Gynecologic Oncology Reports)
Fertility preservation (FP) is an important aspect of the treatment of young women diagnosed with serous borderline ovarian tumors (SBOT), with fertility sparing surgery recommended when possible. Concurrent treatment with aromatase inhibitor letrozole during ovarian stimulation (OS) could be used in women with hormone-sensitive breast cancer, but very little is known in gynecological tumors. Here, we report the cases of 2 young nulliparous women with early stage SBOT who underwent successful OS with letrozole. Patient 1 is 22-years old, FIGO IIB. She had a bilateral ovarian recurrence 5 months after the first surgery. She underwent OS with letrozole (four oocytes were collected and vitrified), followed by cytoreduction. The patient is in complete remission since 2 years. Patient 2 is 27-years old, FIGO IC3, treated by right adnexectomy. Ten months after surgery, she was in complete remission. OS with letrozole was performed and 4 oocytes were retrieved, resulting in 2 blastocysts that were cryopreserved. She had a successful pregnancy after in-vitro fertilization. She underwent a delivery via C-Section for obstetrical reasons that revealed a macroscopic suspicious lesion on the left ovary. Cystectomy was performed during C-section, confirming tumor recurrence. She underwent a second pregnancy uneventfully. During the second C-section, a partial cystectomy and multiples peritoneal biopsies were performed revealing tumor recurrence limited to the left ovary. She underwent left adnexectomy two months after C-Section without any recurrence. In conclusion, our case report described successful oocytes cryopreservation, without changes in the appearance of ovarian cysts, in nulliparous women with early-stage SBOT who underwent OS with simultaneous administration of letrozole.